The EPO-gene in the perspective of human cardiovascular capacity and regulation - Saltin, B. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Through the 1990`es the use of erythropoietin became common among endurance athletes. This EPO misuse has continued and today the EPO micro dosage scheme is widely applied by high performance athletes where aerobic endurance is a key for success. It is likely that several of these athletes would consider switching to EPO gene doping, i.e. inserting the EPO gene in a tissue of their body (muscle, skin) provided its expression could be firmly controlled. This point in gene therapy technology is soon to be achieved, opening for its application in sports. The documentation for a performance enhancing effect of EPO misuse comes both from laboratory experiments and from the sports field. The primary explanation why EPO isso effective is its elevation of the oxygen carrying capacity of the blood, which can be enlarged by 10-20 % or more. What adds to this being so important is that in sports like c.c. skiing, rowing, and swimming, but probably also in bicycling and distance running, the systemic cardiac output is far less than the demand for a blood flow to the exercising muscle. This is also true when the environmental conditions are harsh as at altitude and in a hot climate. The non-optimal muscle perfusion is in part compensated for by the higher arterial oxygen content making the muscles perform at a lower percentage of their peak aerobic capacity and thereby allowing for a better endurance. To this should be added that EPO might have a direct effect on the muscles seeing that receptors for EPO have been identified on their surface. Moreover, EPO may have anti-inflammatory effects, which can be of value in daily training and multi-day events.